Kelet-Közép-Európa és Magyarország agrárgazdasága az Európai Unióhoz való csatlakozás előtt - Buday-Sántha, Attila (Tér és Társadalom, 1998)
As the date of the EU accession approaches, one can more and more often hear opinions within the EU – and especially in Austria – that the date of the accession should be postponed to a later date, and that agricultural assistance (compensations) should be unequally distributed – to the detriment of the newly joining countries. The essay draws the attention to the fact that the accession countries do not make a homogeneous agrarian region, they are countries with different endowments. The emerging problems should be examined and tackled separately in the individual countries. The development of the economy and the raise in the living standards would not only slow down the movement of labour (which is considered as a danger), but the increase of domestic consumption would aiso prevent the production of food surplus.